2002
DOI: 10.1034/j.1399-302x.2002.170405.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection of cytolethal distending toxin activity and cdt genes in Actinobacillus actinomycetemcomitans isolates from geographically diverse populations

Abstract: A cytolethal distending toxin (CDT) found in Actinobacillus actinomycetemcomitans inhibits the eukaryotic cell cycle, which may contribute to the pathogenic potential of the bacterium. The presence of the cdtABC genes and CDT activity were examined in 40 clinical isolates of A. actinomycetemcomitans from Brazil, Kenya, Japan and Sweden. Thirty-nine of 40 cell lysates caused distension of Chinese hamster ovary cells. At least one of the cdt genes was detected in all strains examined. The three cdt genes were de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
41
0
6

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 38 publications
3
41
0
6
Order By: Relevance
“…mRNA levels of cdt were low in serotype a reference strain at the control condition (Table 3), supporting our previous finding that this strain is not as cytotoxic as JP2 (6, 27). However, cdtB was upregulated after prolonged cell exposure in the serotype a strain, suggesting that it may be able to produce high levels of CDT under certain conditions.…”
Section: Discussionsupporting
confidence: 87%
“…mRNA levels of cdt were low in serotype a reference strain at the control condition (Table 3), supporting our previous finding that this strain is not as cytotoxic as JP2 (6, 27). However, cdtB was upregulated after prolonged cell exposure in the serotype a strain, suggesting that it may be able to produce high levels of CDT under certain conditions.…”
Section: Discussionsupporting
confidence: 87%
“…actinomycetemcomitans is the only oral bacterial species known to produce CDT (70). A number of studies collectively support that CDT may be important in the pathogenesis of aggressive periodontitis (1,19,64), although the actual contribution of CDT to this disease is not yet understood. In vitro studies have revealed that CDT stimulated receptor activator of NF-B ligand (RANKL) in human gingival fibroblasts (HGF) (9), which comprise the major cell population of the gingival connective tissue (5).…”
mentioning
confidence: 99%
“…A majority (39/40) of clinical isolates from Brazil, Kenya, Japan and Sweden were also found to harbor the cdt genes and produce the AaCDT (Fabris et al 2002). Although there was some variation in toxin production among the strains, no clear relationship between CDT activity and periodontal status could be found.…”
Section: Occurrence Of Cdts In Clinical Isolates From Various Geograpmentioning
confidence: 87%